Taking the pulse of social cognition: Cardiac afferent activity and interoceptive accuracy modulate emotional egocentricity bias. (December 2021) - von Mohr, Mariana; Finotti, Gianluca; Villani, Valerio; Tsakiris, Manos
Abstract: At the heart of social cognition is our ability to distinguish between self and other and correctly attribute mental and affective states to their origin. Emotional egocentricity bias (EEB) reflects the tendency to use one's own emotional state when relating to others. Although interoception underpins our emotional experience, little is known about its role on how we affectively relate to others. Here, we assessed how cardiac interoceptive impact, manipulated by presenting affective stimuli across different phases of the cardiac cycle coupled with trait-like levels of interoceptive accuracy, modulate the EEB. Individuals with higher interoceptive accuracy displayed an increased EEB when the other's emotional state was presented at the point of maximum interoceptive impact (i.e., at systole), whereas the reverse was observed for individuals with lower interoceptive accuracy. These findings show how interoceptive activity provides the physiological context within which we process other's emotional states in parallel to ours.